Genomic Medicine Revolutionizes Heart Care: A New Standard of Practice - Aastha Parekh; Richa Shah; Foram Shah; Viddhi Bhatt; Dr. Vishwa Mehta (International Journal of Tropical Medicines, 2025)
The integration of genomic and precision medicine into cardiovascular healthcare represents a transformative advancement in addressing the global burden of cardiovascular diseases (CVDs). Precision medicine leverages genomic, proteomic, and metabolomic data to provide personalized care, optimizing treatment outcomes while minimizing adverse effects. Over the past decade, extensive research has highlighted its potential to revolutionize the management of major CVDs, including myocardial infarction, hypertension, and heart failure, which significantly contribute to global morbidity and mortality. Genomic tools, such as polygenic risk scores (PRS) and single nucleotide polymorphisms (SNPs), enhance cardiovascular risk prediction, enabling early interventions and targeted therapies. For example, PRS has demonstrated utility in stratifying individuals with a heightened genetic predisposition to coronary artery disease. Advances in the identification of monogenic variants have also enabled personalized interventions for familial hypercholesterolemia. Furthermore, biomarkers like cardiac troponins, copeptin, and genetic variants in CYP2C19 have refined diagnostic and therapeutic strategies for acute myocardial infarction. Genomic insights into hypertension have unveiled critical pathways, offering potential targets for innovative treatments. Despite the promise, challenges such as ensuring diverse study populations and addressing ethical considerations remain. This evolving paradigm underscores the transformative impact of genomic and precision medicine, heralding a new era of individualized cardiovascular care.
Keywords: Cardiovascular diseases (CVDs); Coronary Artery Disease; Familial Hypercholesterolemia; Genetic Variants; Genomic Insights; Genomic Medicine; Precision medicine; Single Nucleotide Polymorphisms (SNPs); polygenic risk scores (PRS)